Management of inadequate keratinized gingiva and millers class III or IV gingival recession using two-stage free gingival graft procedure - Jacqueline Jacinta Dias; Mohinder Panwar; Manab Kosala (Wolters Kluwer Medknow Publications, 2020)
Background: Prognosis in the management of Millers Class III or IV gingival recession is often fair to poor, which is further decreased by factors such as inadequate keratinized gingiva. Very few modalities show long-term success in the management of gingival recession with inadequate keratinized gingiva, free gingival graft (FGG) being one such technique. Materials and Methods: Ten individuals with Millers Class III or IV recession and inadequate keratinized gingiva were recruited for the study. The first surgical procedure involved the FGG procedure to increase the width of keratinized gingiva (WOKG). Patients were recalled after 3 months for the second surgical procedure, where the flap was coronally advanced. They were recalled 9 months after the second surgery. WOKG was examined at baseline and 3 months (before the second surgical procedure). Recession depth (RD) and clinical attachment level (CAL) was examined at baseline, at 3 months (before the second surgical procedure) and at 12 months (9 months after the second surgical procedure). The percentage of root coverage was measured at 12 months from baseline. Results: Significant increase in WOKG was seen at 3 months. Significant decrease in RD and CAL was observed at 12 months from baseline. The percentage of root coverage was 76.4%. Conclusion: Two-stage FGG procedure can be a successful modality in the management of Millers Class III or IV recession with inadequate keratinized gingiva. This technique improves the prognosis of such compromised cases.